Penerapan Culturally Responsive Teaching (CRT) dalam Pembelajaran Termokimia melalui Konteks Fermentasi Nira (Arenga pinata) sebagai Minuman Tradisional Batak - Ester Debora Togatorop; Marini Damanik (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
21st-century students tend to be less aware of local wisdom, necessitating a learning approach that integrates culture into the learning process. This study aims to determine the differences in learning outcomes and inclusive attitudes of students taught using the Batak culture-based Culturally Responsive Teaching (CRT) model compared to direct instruction, and to measure the model's influence on thermochemistry. The study used a quantitative approach with a quasi-experimental design and purposive sampling technique on 11th-grade science students of SMA Negeri 10 Medan in the 2025/2026 academic year. The results showed that the Batak culture-based CRT model had a significant effect on student learning outcomes (t = 4.77; Cohen's d = 1.212, large category) and students' inclusive attitudes (t = 3.103; Cohen's d = 0.787–2.87, medium to very large category). It was concluded that the integration of Batak culture in CRT learning effectively improved students' learning outcomes and inclusive attitudes in thermochemistry.